Synergistic effect of molar ratio on lead removal by Zn-Al layered double hydroxide - N.A., Awang; W.N., Wan Salleh; S.Z.N., Ahmad; N.A., Mohd Razali; Norazlianie, Sazali; A.F., Ismail (Elsevier B.V., 2025)
This study investigates the removal of Pb(II) ions from aqueous solutions using Zinc Aluminum Layered Double Hydroxide (Zn/Al LDH) synthesized at different Zn molar ratios (1:1, 1:2, 2:1, 1:3, and 3:1). The adsorption efficiency of Zn/Al LDH was evaluated through batch adsorption experiments, and the effects of varying the molar ratios on adsorption capacity were examined. Characterization techniques including X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET), field emission scanning electron microscopy (FESEM), energy dispersive X-ray analysis (EDX), Fourier-transform infrared (FTIR) as well as thermogravimetric analysis (TGA-DTG) were employed to analyze the structural and morphological properties of the synthesized materials. The Langmuir, Freundlich and Temkin isotherm models were applied to describe the adsorption process, revealing that the adsorption is best described by the Langmuir isotherm, indicating monolayer adsorption. The results demonstrated that the LDH with a 1:2 M ratio exhibited the highest adsorption capacity with 275.28 mg/g, attributed to its greater specific surface area and optimal distribution of active sites. The adsorption of Pb(II) ions onto Zn/Al LDH likely involves multiple mechanisms, such as surface adsorption, ion exchange, and chemical interactions. This study highlights the potential of Zn/Al LDH as an effective adsorbent for the removal of heavy metals from wastewater, with the molar ratio of Zn to Al playing a crucial role in determining the adsorption efficiency.